ANALISIS PENERAPAN SAK ETAP (STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK) DALAM PENYUSUNAN DAN PENYAJIAN LAPORAN KEUANGAN PADA PT CIPTA AGUNG LESTARI - Esti Damayanti, SE., M.Si.; Nurjannah Citradewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
SAK ETAP is an accounting standard set by IAI with the purpose of facilitating medium enterprises in preparing and presenting the financial statements to be more informative and relevant, so it will be interpretated by the external users, such as investors and creditors to providing financing for SME’s. The purpose of this research is to determine the presentation of PT Cipta Agung Lestari financial statements by an entity’s financial accounting standards without public accountability (SAK ETAP). This research used a description comparative method with secondary data sources and the results of this research indicate that the presentation of PT Cipta Agung Lestari financial statements are not yet complied with SAK ETAP, because the company has not applied adjustment journals in accounting cycle and has not presented statement of owner’s equity, cash flow statement and notes to financial statement.